The Rise of the Seljuqs and their State in Central Asia - Islam, Arshad (INSInet Publications, 2012)
The Seljuqs, who arose in the 11thcentury CE in Central Asia, created one of the largest Muslim Empires in the Middle East, unifying the Muslim lands of the Abbasid east and giving a new impetus to the course of Muslim history. They were the most prominent Turkic Muslim dynasty prior to the Ottomans, with dominion throughout central Asia, Iran, Iraq, Kirman, Syria and Anatolia; it was the Seljuq threat to the Byzantine Empire that precipitated the Crusades. However, little is generally known of the origins and rise of the Suljuqs; this paper explores the course of the genesis of Seljuq power and authority. It traces the rise of the Seljuqs from a minor branch of a Turkic tribe through their incorporation into the fabric of the dwindling Samanid province, then the various manoeuvresand struggles that took place between them and rival Turkic peoples – the Ghaznavids and the Qarakhanids and the various wars for supremacy in Khurasan. It then charts the life and campaigns of Sultan Jalaluddin Malikshah, Sultan Rukn Al-Dunya Tughril Beg, relations with the Abbasid Caliphs (including marriage), the accession of Sultan Alp Arslan, campaigns against the Byzantnies, along with numerous intra-Seljuq wars of succession and rebellions, and the important role of the vizier Nizamul Mulk. Based mainly on Arabic, Persian, Urdu and English sources, the study focuses on the intellectual legacy of the Seljuqs, including their interest in the progress of science and philosophy